Direct Aulacaspis yasumatsui Infestation of Pre-Harvest Cycas Seeds Reduces Germination and Performance of Seedlings - Thomas E. Marler (Horticulturae, 2021)
The invasion of numerous countries by the armored scale Aulacaspis yasumatsui Takagi has caused widespread mortality of host Cycas species. Few studies have looked at reproductive biology responses of host plants to the herbivore. This study was conducted to determine the influence of direct Cycas seed integument infestation of A. yasumatsui on germination and seedling performance. An observational study in a Tinian ex situ Cycas micronesica K.D. Hill garden revealed that germination percentage was reduced two-thirds by heavy pre-harvest integument infestation, and more than half of the seedlings from infested seeds died in the nursery. Multi-year mortality of plants was six times greater for plants from habitats with infested seeds than for plants from minimally infested habitats. Stem height of nine-year-old plants from habitats with infested seeds was 64% of that of plants from habitats with un-infested seeds. A controlled study in a Philippine ex situ C. micronesica and Cycas edentata de Laub. garden corroborated these findings. Germination of infested seeds was about 30% of that for un-infested seeds. Seedling mortality in the nursery following experimental infestation of seed integuments with A. yasumatsui during seed maturation was about 50%, but was minimal for seedlings from un-infested seeds. These results indicate that limitations in regeneration and recruitment of host Cycas plants following A. yasumatsui herbivory may be partly due to the influence of direct seed infestations. Conservationists may use this new knowledge to improve in situ seed selection criteria and use prophylactic treatments to ensure lack of integument infestations for ex situ gardens.